2016
DOI: 10.1177/0260107916643469
|View full text |Cite
|
Sign up to set email alerts
|

Herd Behaviour and Path Dependence in News Markets: Towards an Economic Theory of Scandal Formation

Abstract: Media phenomena coined as issue attention cycles, media hypes or scandals describe processes in which attention towards issues and news frames converges in news markets. But what drives these processes? This article explores a new theoretical framework, which draws on Economic Theory (i.e., Path Dependence Theory, Principal-Agent Theory, Herd Behaviour Theory and Behavioural Economic Theory), incorporates results from journalism and mass communication research and discusses a process in which journalists and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 93 publications
0
13
0
1
Order By: Relevance
“…There has been extensive research into herd behaviour and interdependence within the fields of behavioural economics and social psychology, in which studies have shown that an individual's bias towards a particular group is a significant contributor towards their social relations (Hogg 2013). This behaviour has also been proposed as a factor in determining how stories are framed in the media (Wilczek 2016).…”
Section: Bellwether Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been extensive research into herd behaviour and interdependence within the fields of behavioural economics and social psychology, in which studies have shown that an individual's bias towards a particular group is a significant contributor towards their social relations (Hogg 2013). This behaviour has also been proposed as a factor in determining how stories are framed in the media (Wilczek 2016).…”
Section: Bellwether Behaviourmentioning
confidence: 99%
“…The news media is an important information source for much of the world's population, as it feeds into opinions and choices (McCombs and Shaw 1972;McCombs et al 1997;Wilczek 2016). Frequently referred to as the 'gatekeepers of information' , journalists have been shown to play a powerful role in influencing public opinion through determining what stories (or elements thereof ) are presented to the public, how content is framed, which elements are emphasized, and how the public forms associations between topics covered by the news (Guo et al 2012;Wilczek 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivations to act may result in unclear risks or benefits to the whistleblower, as altruistic intentions can cloud any risk/benefit analysis judgments. Wilczek (2016) outlined several cognitive processes that may aid in motivating whistleblowers to take action. The availability heuristic, or mental shortcut based on previous knowledge that is recalled when situationally appropriate, according to Wilczek, may simply buttress a whistleblower’s perceptions of wrongdoing and the need to disclose unethical acts.…”
Section: The Whistleblower: a Conceptual Definitionmentioning
confidence: 99%
“…For example, seeing similar wrongdoing being reported by journalists may confirm a potential whistleblower’s motivation to disclose, as the observed confirmation is cognitively relevant to the whistleblower. In addition, whistleblowers may be overconfident in their ability to predict the outcomes of their actions, be convinced they remain in control of the situation, believe they have planned their actions satisfactorily, or believe they may receive recognition for their disclosures (Wilczek, 2016, p. 147).…”
Section: The Whistleblower: a Conceptual Definitionmentioning
confidence: 99%